Protective Effects of Radix Sophorae Flavescentis Carbonisata-Based Carbon Dots Against Ethanol‐Induced Acute Gastric Ulcer in Rats: Anti-Inflammatory and Antioxidant Activities - Hu J; Luo J; Zhang M; Wu J; Zhang Y; Kong H; Qu H; Cheng G; Zhao Y (International Journal of Nanomedicine, 2021)
Jie Hu,1,* Juan Luo,1,* Meiling Zhang,1 Jiashu Wu,1 Yue Zhang,2 Hui Kong,1 Huihua Qu,3 Guoliang Cheng,4 Yan Zhao1 1School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China; 2School of Life Science, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China; 3Center of Scientific Experiment, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China; 4State Key Laboratory of Generic Manufacture Technology of Chinese Traditional Medicine, Lunan Pharmaceutical Group Co., Ltd., Linyi, 276000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan ZhaoSchool of Traditional Chinese Medicine, Beijing University of Chinese Medicine, No. 11 Bei San Huan Dong Lu, Chaoyang District, Beijing, 100029, People’s Republic of ChinaTel +86 010-62486705Email zhaoyandr@bucm.edu.cnGuoliang ChengState Key Laboratory of Generic Manufacture Technology of Chinese Traditional Medicine, Lunan Pharmaceutical Group Co., Ltd., No. 209 Hong Qi Lu, Lanshan District, Linyi, 276000, Shandong Province, People’s Republic of ChinaTel +86 18905391156Email 18905391156@163.comAim: To explore the effects of Radix Sophorae Flavescentis carbonisata-based carbon dots (RSFC-CDs) on an ethanol-induced acute gastric ulcer rat model.Methods: The structure, optical properties, functional groups and elemental composition of RSFC-CDs synthesized by one-step pyrolysis were characterized. The gastric protective effects of RSFC-CDs were evaluated and confirmed by applying a rat model of ethanol-induced acute gastric ulcers. The underlying mechanisms were investigated through the nuclear factor-kappa B (NF-κB) signalling pathway and oxidative stress.Results: RSFC-CDs with a diameter ranging from 2– 3 nm mainly showed gastric protective effects by reducing the levels of NF-κB, tumour necrosis factor-α (TNF-α), interleukin (IL)-6, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), glutathione (GSH), malondialdehyde (MDA) and inducible nitric oxide synthase (iNOS) to inhibit ethanol-induced inflammation and oxidative stress.Conclusion: RSFC-CDs have anti-inflammatory and anti-oxidative effects, making them promising for application in ethanol-induced gastric injury.Keywords: carbon dots, Radix Sophorae Flavescentis, gastroprotection, anti-inflammatory, antioxidant